Thermoplastic compositions containing masterbatches of stick-slip modifiers

By using thermoplastic silicone hardener as stick-slip modifiers in thermoplastic materials, the problem of poor tribological and stick-slip characteristics of thermoplastic materials in frictional environments is solved, and noise reduction, wear reduction and material durability are improved.

JP7666926B2Active Publication Date: 2025-04-22DDP SPECIALTY ELECTRONIC MATERIALS US 9 LLC +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020552793
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-04-05
Filing Date
2019-04-04
Publication Date
2025-04-22
Estimated Expiration
2039-04-04

AI Technical Summary

Technical Problem

Existing thermoplastic materials exhibit poor tribological and stick-slip properties in certain frictional environments, resulting in increased noise generation and wear.

Method used

Thermoplastic silicone vulcanizates are used as stick-slip modifiers, and the masterbatch containing the silicone hardener is synthesized and mixed with thermoplastic elastomers to form a thermoplastic material with improved tribological properties.

Benefits of technology

Effectively reduce or eliminate stick-slip interactions of thermoplastic materials in friction environments, reduce noise generation and wear, and improve material durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666926000001
    Figure 0007666926000001
  • Figure 0007666926000002
    Figure 0007666926000002
  • Figure 0007666926000003
    Figure 0007666926000003
Patent Text Reader

Abstract

The present disclosure relates to molded articles made from a thermoplastic material, which may be a thermoplastic elastomeric material containing a masterbatch of a stick-slip modifier with one or more thermoplastic silicone vulcanizates, assemblies including the molded articles, and methods for making the molded articles. [Selection diagram] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to molded articles, assemblies including molded articles, and methods of making molded articles made from a thermoplastic material, which may be a thermoplastic elastomeric material containing a masterbatch of a stick-slip modifier with one or more thermoplastic silicone vulcanizates. [Background technology]

[0002] Thermoplastic materials are plastic materials that become pliable or moldable above a certain temperature and solidify upon cooling. When reheated, thermoplastic materials can be remolded into new shapes. In contrast, thermoset materials are plastics that are irreversibly hardened from soft solid or viscous liquid prepolymers or resins; once hardened / solidified, thermoset materials cannot be remolded into new shapes when reheated. Thermoplastic polymers, such as polyamides, polyesters, polyphenylene sulfides, polyoxymethylene, polyolefins, styrene polymers, and polycarbonates, are characterized by exceptional mechanical and electrical properties, as well as excellent moldability and chemical resistance. However, these polymers exhibit poor tribological and / or stick-slip properties when utilized in some frictional environments, such as, for example, plastic-metal and plastic-plastic interfaces.

[0003] Thermoplastic elastomers (TPEs) are polymer-based materials that have both plastic and rubber properties. As shown above, TPEs can be reprocessed at high temperatures. This reprocessing ability is a major advantage of TPEs over chemically crosslinked rubbers, as it allows for recycling of processed parts, resulting in a significant reduction in scrap.

[0004] Generally, two main types of thermoplastic elastomers are known: block copolymer TPEs and simple blend TPEs (physical blends).

[0005] Block copolymer TPEs include: (i) blocks or segments that are termed hard or rigid (i.e., have thermoplastic behavior), typically these have a melting point or glass transition temperature above ambient temperature; and (ii) Blocks or segments that are termed soft (ie, have elastomeric behavior) and that are pliable or flexible; these typically have a low glass transition temperature (Tg) or a melting point significantly below room temperature. The expression "low glass transition temperature" is understood to mean a glass transition temperature Tg below 15°C, preferably below 0°C, advantageously below -15°C, more advantageously below -30°C and possibly below -50°C.

[0006] In block copolymer thermoplastic elastomers, the hard segments aggregate to form distinct microphases and act as physical crosslinks for the soft phase, thereby imparting rubber-like properties at room temperature. At elevated temperatures, the hard segments melt or soften, allowing the copolymer to flow and be processed. The hard blocks are typically based on polyamides, polyurethanes, polyesters, polystyrenes, polyolefins, or mixtures thereof. The soft blocks are typically based on polyethers, polyesters, polyolefins, and copolymers or blends thereof.

[0007] TPEs, called simple or physical blends, can be obtained by homogeneously mixing an elastomeric component with a thermoplastic resin.

[0008] Articles, such as components of an assembly, made from thermoplastic polymers are often designed to slide or rub during operation against one or more other components also made from thermoplastic polymers. The sliding and / or rubbing between adjacent surfaces does not always produce a constant frictional force and instead tends to oscillate between sticking and sliding, a phenomenon commonly referred to as "stick-slip."

[0009] The term stick-slip is used to describe the manner in which two opposing surfaces or objects slide relative to one another in response to static and kinetic friction. Static friction is intended to mean the friction between two objects that do not move relative to one another. In order for two objects to move relative to one another while remaining in contact, a force greater than the static friction force must be applied to one of the objects. Kinetic friction is intended to mean the friction created when two objects move relative to one another while in contact. Friction between two surfaces may increase or decrease during movement depending on various factors, such as the speed at which the movement occurs.

[0010] An unfortunate consequence of stick-slip motion is the production of an audible and often unpleasant "squeaky" noise as the stick-slip occurs. Such noise is particularly undesirable when used in consumer electronics and vehicle interiors. The production of this type of noise is undesirable during use of the product and can be very irritating and annoying to the user.

[0011] To try to avoid possible noise generation, materials such as fabric and / or foam may be added or placed between the two thermoplastic materials, for example, however this is undesirable as it can be expensive and indeed require complex adjustments of parts and machinery.

[0012] Lubricating compositions have been applied to thermoplastic polymers to improve friction and wear properties, but certain applications, such as food handling, clothing manufacturing, and volatile environments, have prohibited the use of many promising lubricants due to potential contamination. In addition, lubricants have also been incorporated directly into thermoplastic polymers before they are made into molded articles. Many materials, such as solid lubricants, fibers (e.g., graphite, mica, silica, talc, boron nitride, and molybdenum sulfide), paraffin wax, petroleum and synthetic lubricants, and polymers (e.g., polyethylene and polytetrafluoroethylene), in various combinations, have been added to thermoplastic polymers to improve their lubricating properties. Coatings based on fluoropolymers are known, but are generally expensive, can be difficult to apply, and the coated end products often lack flexibility. Recent advances include the commercial availability of "off the shelf" "squeak-resistant" polycarbonate / acrylonitrile-butadiene-styrene (PC / ABS) grades.

[0013] A masterbatch is typically a solid additive for a plastic or other polymer that is used to impart a desired property to that plastic or other polymer. A masterbatch is a concentrated mixture of additives that are typically encapsulated in a carrier resin during a process that involves heat, which is then cooled and cut into granules. This improves the desired properties of the polymer. Masterbatches are typically in solid form at ambient temperature, usually in pelletized form. Siloxane masterbatches are typically pelletized microdispersions of siloxane polymers, contained in a variety of different plastic carrier resins at loadings of up to 50%. Siloxane masterbatches are manufactured in solid form for ease of use. They typically contain 25-50% siloxane polymer (usually 1 million mm) dispersed in a variety of thermoplastic resins with an average particle size of, for example, 5 μm. 2 ·s -1 (cSt), typically 15 million mm 2 ·s -1 (gum having a viscosity of more than (cSt)).

[0014] Masterbatches of uncured organopolysiloxane polymers in thermoplastic resins are a proven solution for improving the surface performance of thermoplastic resins. Siloxane masterbatches, which contain high molecular weight siloxane polymers dispersed in a variety of thermoplastic resins, have been used successfully in automotive interior and exterior parts, consumer applications such as laptop and cell phone cases, and in the tubing and film markets. The siloxane polymers migrate to the surface in the melt phase and impart resistance to scuffing and marring without the adverse effects of additive leaching of small molecule additives.

[0015] The most commonly used uncured organopolysiloxane polymers have the shortest chain length possible, e.g. 0.65 mm. 2 ·s -1 From hexamethyldisiloxane with a viscosity of 10 6 mm 2 ·s -1 A linear PDMS (polydimethylsiloxane) of various viscosities ranging from 0.1 to 1.0 cSt to a polymer often called a silicone gum. PDMS gums are typically around 10 6 mm 2 ·s -1 (cSt) or higher. High viscosity diorganopolysiloxane polymers (e.g., ≥ 1,000,000 mm 2 ·s -1 Viscosity values ​​in cSt (cSt) can be measured using an AR2000 rheometer from TA Instruments, New Castle, DE, USA or a suitable Brookfield viscometer using the spindle most appropriate for the viscosity being measured. However, the polymer may also be a silicone gum, which is a high molecular weight polymer with a very high viscosity. Gums typically have a viscosity of at least 2,000,000 mm at 25°C. 2 ·s -1(cSt), but usually have a much larger viscosity. Therefore, gums are often characterized by their Williams plasticity value according to ASTM D-926-08, taking into account that the viscosity can be very difficult to measure. Instead of utilizing Williams plasticity, gums can also be graded by their Shore A hardness, measured for example by ASTM D2240-03, which is typically at least 30.

[0016] Another method of modifying TPEs is by crosslinking the elastomeric component of the TPE during mixing to form a special form of TPE known in the art as a thermoplastic vulcanizate (TPV) in which the crosslinked elastomeric phase is insoluble and non-flowable at elevated temperatures; TPVs generally exhibit improved oil and solvent resistance and reduced compression set compared to simple blends. Typically, TPVs are formed by a process known as dynamic vulcanization, in which the ingredients needed to make an elastomer (e.g., polymer, crosslinker, and catalyst) and a thermoplastic matrix are mixed together and the elastomer is cured simultaneously to form a "co-continuous blend" of the thermoplastic matrix and the elastomer.

[0017] Many such TPVs are known in the art, including some in which the thermoplastic component is an organic, non-silicone polymer, while the crosslinked elastomeric component may be a silicone polymer that has been cured with the aid of a crosslinker and / or catalyst during the mixing process. Such TPVs may be referred to as thermoplastic silicone vulcanizates or TPSiVs after manufacture, and TPVs, such as TPSiVs, can be processed by conventional techniques, such as extrusion, vacuum forming, injection molding, blow molding, 3D printing, or compression molding, to produce plastic parts.

[0018] However, the addition of many of these additives in various combinations to thermoplastic polymers has improved tribological properties while degrading other desirable physical and mechanical properties. Although some lubricants have been found to be satisfactory in the short term at low speeds and low loads, the desirable friction properties of many of these lubricants degrade significantly over the long term as loads increase. Summary of the Invention [Means for solving the problem]

[0019] It has now been determined that the use of thermoplastic silicone vulcanizates can impart enhanced resistance to stick-slip interactions to thermoplastic materials, thereby minimizing or completely eliminating audible noise and reducing wear, which can therefore be utilized to reduce the manifestation of the stick-slip phenomenon.

[0020] In this specification, (A) one or more thermoplastic organic materials; (B) (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier comprising A molded article of a thermoplastic material comprising a blend of A molded article is provided in which the masterbatch (B) contains 20-60% by weight of crosslinked silicone elastomer based on the weight of (B1)+(B2)+(B3), and the thermoplastic elastomer composition contains a total of 0.2-25% by weight of crosslinked silicone elastomer based on the weight of (A)+(B). The thermoplastic material may be a thermoplastic elastomer material.

[0021] Also disclosed is an assembly including a molded article in frictional contact with a sliding member, the molded article and the sliding member being configured to move relative to one another while remaining in contact, the molded article comprising: (A) one or more thermoplastic organic materials; (B) (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier comprising The thermoplastic material includes a blend of There is also provided an assembly, in which in the masterbatch (B) 20-60% by weight of crosslinked silicone elastomer is present, based on the weight of (B1)+(B2)+(B3), and in the thermoplastic elastomer composition there is a total of 0.2-25% by weight of crosslinked silicone elastomer, based on the weight of (A)+(B). The thermoplastic material may be a thermoplastic elastomer material.

[0022] Also provided is a method for producing a molded article using the thermoplastic composition described above, the method comprising: 26. A method according to claim 25 for preparing a compound of the formula (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch (B) containing (i) mixing the components used to make the silicone elastomer (B2) to form a silicone composition; (ii) blending the silicone composition with one or more thermoplastic organic materials; (iii) dynamically vulcanizing the silicone composition to form a silicone elastomer (B2) in the preparation of the silicone elastomer B2; and / or (iv) introducing (B3) during step (ii) or after step (iii) when B2 is present; The method comprises the steps of: The masterbatch (B) contains 20 to 60% by weight of a crosslinked silicone elastomer, based on the weight of (B1)+(B2)+(B3); blending the resulting masterbatch with one or more thermoplastic organic materials (A) in an amount such that the thermoplastic elastomer composition has a total of 0.2 to 25 weight percent crosslinked silicone elastomer, based on the weight of (A)+(B); As well as forming a molded article from a thermoplastic material, the thermoplastic material may be a thermoplastic elastomer material.

[0023] Also provided herein is the use of a thermoplastic silicone vulcanizate in a masterbatch to reduce the occurrence of stick-slip interactions with thermoplastic materials.

[0024] The use of the masterbatch as described above maintains good dispersion and interaction within the thermoplastic material. Furthermore, the use of silicone rubber vulcanizate dispersions results in compounds that exhibit good surface appearance and minimize the migration of silicone oil from the thermoplastic material over time. In addition, the need to use fluoropolymers is avoided. An additional advantage of using the masterbatch as described above is the ease of use, which allows the solution to be used in any compounder or injection molding machine. This allows for greater flexibility in dosage and therefore is more cost-effective since it allows for direct modification of the thermoplastic resin (e.g., the polycarbonate / acrylonitrile-butadiene-styrene (PC / ABS) material used) as opposed to current options such as anti-squeak coatings or chemically modified pre-made materials (e.g., PC / ABS combinations).

[0025] The present disclosure particularly relates to polymer compositions that can be used to make molded parts that reduce or even eliminate noise generation due to stick / slip effects as the parts slide relative to one another. Particularly advantageously, compositions made according to the present disclosure can be used to form opposing sliding members that have reduced stick-slip properties, thereby preventing the sliding members from making noise during use.

[0026] Introducing a silicone vulcanization phase into a thermoplastic resin can combine the above advantages due to the flexibility and high elasticity of silicone after crosslinking, the low Tg of polydimethylsiloxane, and the surface modification brought about by the surface silicone domains. These advantages can be observed even at high Si contents, and the crosslinking of silicone in finite particles allows for the fusion in larger sized silicone domains. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] For the avoidance of doubt, silanes and siloxanes are compounds that contain silicon. · Silanes are compounds derived from Si-H4. Silanes often contain at least one Si-C bond and, unless otherwise specified, only one Si atom. ·Polysiloxanes contain multiple Si-O-Si- bonds forming a polymer chain, the backbone of the polymer chain being composed of -(Si-O)- repeating units. Organopolysiloxanes contain -(Si-O)- repeating units where at least one Si atom bears at least one organic group. "Organic" means containing at least one carbon atom. An organic group is a chemical group that contains at least one carbon atom.

[0028] Polysiloxanes include end groups and pendant groups. End groups are chemical groups located on Si atoms that are at the end of a polymer chain. Pendant groups are groups located on Si atoms where the Si atom is not at the end of a polymer chain. Typically, organopolysiloxanes include a mixture of the following structures: [ka] (wherein M, D, T, and Q each independently represent a functional group of the structural group of the organopolysiloxane). Specifically, M is a monofunctional group RSiO 1 / 2 D represents the difunctional group RSiO2 / 2; T represents the trifunctional group RSiO 3 / 2 Q represents a tetrafunctional group SiO 4 / 2Thus, for example, a linear organopolysiloxane may have a backbone of D units terminated with M units, and a branched organopolysiloxane may have a backbone of D units interspersed with, for example, T and / or Q units.

[0029] A polymer is a compound that contains repeating units, which typically form at least one polymer chain. A polymer may be a homopolymer or a copolymer. A homopolymer is a polymer formed from only one type of monomer. A copolymer is a polymer formed from at least two different types of monomer. If the repeating units contain carbon atoms, the polymer is called an organic polymer.

[0030] A crosslinking reaction is a reaction in which two or more molecules (at least one of which is a polymer) bond together to solidify or harden the polymer. A crosslinking agent is a compound capable of causing a crosslinking reaction of a polymer.

[0031] The one or more thermoplastic organic materials (B1) may be polycarbonate (PC); blends of polycarbonate with other polymers, such as polycarbonate / acrylonitrile-butadiene-styrene (PC / ABS) blends and polycarbonate-polybutylene terephthalate (PC / PBT) blends; polycaprolactam (nylon-6), polylauryllactam (nylon-12), polyhexamethylene adipamide (nylon-6,6), polyhexamethylene dodecane amide (nylon-6,12), poly(hexamethylene sebacamide ( Polyamides, exemplified by nylons such as nylon 6,10), and blends of nylon with other polymers; polyesters, exemplified by polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN); polyphenylene ether (PPE), polyphenylene oxide (PPO), and blends of PPE or PPO with styrenic resins, such as high impact polystyrene (HIPS), polystyrene, acrylonitrile-butadiene-styrene (ABS), and styrene-acrylonitrile resin (SAN). The thermoplastic organic material (B1) may be selected from the following: styrene-based materials, exemplified by polyphenylene sulfide (PPS), polyethersulfone (PES), polyaramid, polyimide, phenyl-containing resins with rigid rod structure, ABS (acrylonitrile-butadiene-styrene), polystyrene (PS), and HIPS; polyacrylates; halogenated plastics, exemplified by polyvinyl chloride, fluoroplastics, and any other halogenated plastics; polyketones; polymethyl methacrylate (PMMA); polyolefins, exemplified by polypropylene (PP), polyethylene (PE) (including high density polyethylene (HDPE) and low density polyethylene (LDPE)), polybutene (PB), and copolymers and blends of polyolefins; thermoplastic elastomers, such as thermoplastic urethanes, thermoplastic polyolefin-based elastomers, thermoplastic vulcanizates; styrene ethylene butylene styrene (SEBS) copolymers; and natural products, such as cellulose, rayon, and polylactic acid. As indicated above, the one or more thermoplastic organic materials (B1) may be a mixture of two or more of the above-mentioned thermoplastic resins.

[0032] Component (B1) is present in an amount of 40 to 80% by weight of the total weight of component B, alternatively 45 to 70% by weight of the total weight of component B.

[0033] The silicone elastomer (B2) can be prepared by curing one of the following compositions: (B2a1) a diorganopolysiloxane having an average of at least two alkenyl groups per molecule; (i) an organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, a hydrosilylation catalyst (B2a3), and an optional catalyst inhibitor (B2a5); or (ii) Radical initiator (B2a4).

[0034] Alternatively, the silicone elastomer (B2) may be prepared by curing a composition containing: Silanol-terminated diorganopolysiloxanes (B2b1), Organopolysiloxanes (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, and Condensation catalyst (B2b3).

[0035] The silicone elastomer present in the masterbatch is present in an amount from 20 to 60 weight percent of the total weight of component (B); alternatively from 30 to 55 weight percent of the total weight of component (B).

[0036] Diorganopolysiloxanes (B2a1) containing an average of at least two alkenyl groups per molecule The diorganopolysiloxane polymer (B2a1) has a viscosity of at least 100,000 mm at 25° C. 2 ·s -1 (cSt), or at least 1,000,000 mm at 25°C 2 ·s -1(cSt). The silicon-bonded organic groups of component (B2a1) are independently selected from hydrocarbon or halogenated hydrocarbon groups. These may be specifically exemplified by alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, and hexyl; cycloalkyl groups, such as cyclohexyl and cycloheptyl; alkenyl groups having 2 to 20 carbon atoms, such as vinyl, allyl, and hexenyl; aryl groups having 6 to 12 carbon atoms, such as phenyl, tolyl, and xylyl; aralkyl groups having 7 to 20 carbon atoms, such as benzyl and phenethyl; and halogenated alkyl groups having 1 to 20 carbon atoms, such as 3,3,3-trifluoropropyl and chloromethyl. Of course, it will be understood that these groups are selected so that the diorganopolysiloxane has a glass transition temperature (or melting point) below room temperature, such that the component forms an elastomer upon curing. Methyl preferably constitutes at least 85 mole percent, and more preferably at least 90 mole percent, of the silicon-bonded organic groups in component (B2a1).

[0037] Thus, the polydiorganosiloxane (B2a1) may be a homopolymer, copolymer or terpolymer containing such organic groups. Examples include fluids or gums containing, in particular, dimethylsiloxy, dimethylsiloxy and phenylmethylsiloxy units; dimethylsiloxy and diphenylsiloxy units; and dimethylsiloxy, diphenylsiloxy and phenylmethylsiloxy units. The molecular structure is also not critical, with linear and partially branched linear being examples, although linear structures of dimethylsiloxy units are preferred. Examples include α,ω-vinyldimethylsiloxy polydimethylsiloxane, α,ω-vinyldimethylsiloxy copolymers of methylvinylsiloxane and dimethylsiloxane units, and / or α,ω-trimethylsiloxy copolymers of methylvinylsiloxane and dimethylsiloxane units.

[0038] The diorganopolysiloxane polymer (B2a1) has a viscosity of at least 100,000 mm at 25° C. 2 ·s -1 (cSt), but typically at least 1 million mm 2 ·s -1 (cSt), which can be measured by using an AR2000 rheometer from TA Instruments, New Castle, DE, USA, or a suitable Brookfield viscometer equipped with the spindle most suitable for the viscosity to be measured. The diorganopolysiloxane polymer (B2a1) may optionally be a gum characterized by a Williams plasticity value of at least 100 mm / 100, measured by ASTM D-926-08 using a Williams parallel plate plastometer, taking into account that viscosity values ​​can be very high and therefore very difficult to determine accurately. Instead of utilizing the Williams plasticity, the gums may also be graded by their Shore A hardness, measured for example by ASTM D2240-03, which is typically at least 30. The diorganopolysiloxane polymer (B2a1) may optionally be modified with small amounts of non-reactive silicones, such as trimethylsilyl-terminated polydimethylsiloxanes. In one alternative, the diorganopolysiloxane polymer (B2a1) is a gum.

[0039] Examples of the alkenyl groups in the diorganopolysiloxane (B2a1) include vinyl, hexenyl, allyl, butenyl, pentenyl, and heptenyl groups. Examples of the organic groups bonded to silicon other than the alkenyl groups in the diorganopolysiloxane polymer (B2a1) include methyl, ethyl, propyl, butyl, pentyl, hexyl, or similar alkyl groups; or phenyl, tolyl, xylyl, or similar aryl groups.

[0040] Organopolysiloxanes (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule The organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule may be, for example, a low molecular weight organosilicon resin or a short- or long-chain organosiloxane polymer, which may be linear or cyclic. The silicon-bonded organic groups of component (B2a2) are independently selected from any of the hydrocarbon or halogenated hydrocarbon groups described above in connection with the diorganopolysiloxanes (B2a1 and B2b1), including preferred embodiments thereof. The molecular structure of component (B2a2) is also not critical and is exemplified by linear, partially branched linear, branched, cyclic, and network structures, with linear polymers or copolymers being preferred, and this component must be effective in curing components (B2a1) and (B2b1). (B2a2) preferably has at least three silicon-bonded hydrogen atoms per molecule, which can react with alkenyl or other aliphatically unsaturated groups of the diorganopolysiloxane polymer (B2a1) and with the -OH groups of (B2b1), as will be explained in more detail below. The position of the silicon-bonded hydrogen in component (B2a2) is not critical; that is, the Si-H groups can be terminal groups, or pendant groups at non-terminal positions along the molecular chain, or both. In order to ensure crosslinking when (B2a2) has only two Si-H bonds, it is necessary that at least a portion of each polymer (B2a1) or (B2b1) has at least three groups capable of reacting with the (B2a2) molecule. Organopolysiloxanes (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule can be, for example, those having the general formula: R 3 R 4 2SiO(R 4 2SiO) p (R 4 HSiO) q SiR 4 2R 3 or [ka] (In the formula, R 4means an alkyl or aryl group having up to 10 carbon atoms, R 3 is the group R 4 or a hydrogen atom, p has a value of 0 to 20, q has a value of 1 to 70, and there are at least 2 or 3 hydrogen atoms bonded to silicon per molecule). R4 may be, for example, a lower alkyl group having 1 to 3 carbon atoms, such as a methyl group. The organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule has a viscosity of, for example, 0.5 to 1000 mm at 25°C. 2 ·s -1 (cSt), or 2 to 100 mm at 25°C 2 ·s -1 cSt), or 5 to 60 mm 2 ·s -1 (cSt), typically measured using a Brookfield viscometer and a spindle most appropriate for the viscosity range being measured. The average degree of polymerization of (B2a2) may be, for example, in the range of 30 to 400 siloxane units per molecule. Component (B2a2) typically has a viscosity of 0.5 to 1000 mm at 25°C. 2 ·s -1 can be exemplified by the following siloxanes having a viscosity of (cSt): low molecular weight siloxanes such as PhSi(OSiMe2H)3; Trimethylsiloxy end-capped methylhydridopolysiloxane; Trimethylsiloxy end-capped dimethylsiloxane-methylhydridosiloxane copolymer; Dimethylhydridosiloxy end-capped dimethylpolysiloxane; dimethylhydrogensiloxy end-capped methylhydrogenpolysiloxane; Dimethylhydridosiloxy end-capped dimethylsiloxane-methylhydridosiloxane copolymers; Cyclic methylhydrogen polysiloxane; Cyclic dimethylsiloxane-methylhydridosiloxane copolymer; Tetrakis(dimethylhydrogensiloxy)silane; (CH3)2HSiO 1 / 2 , (CH3)3SiO 1 / 2 , and SiO 4 / 2 a silicone resin comprising a unit; and (CH3)2HSiO 1 / 2 , (CH3)3SiO 1 / 2 , CH3SiO 3 / 2 , PhSiO 3 / 2 , and SiO 4 / 2 Silicone resin composed of units (B2a2) may comprise a mixture of two or more of these materials.

[0041] The molar ratio of Si-H groups in (B2a2) to aliphatically unsaturated groups in the diorganopolysiloxane polymer (B2a1) is preferably at least 1:1, and may be up to 8:1 or 10:1. For example, the molar ratio of Si-H groups to aliphatically unsaturated groups is in the range of 1.5:1 to 5:1.

[0042] (B2a2) is used at a level such that the molar ratio of Si-H therein to Si-OH in component (B2b1) is from about 0.5 to 10, preferably from 1 to 5, and most preferably about 1.5.

[0043] These Si-H functional materials are well known in the art and many of them are commercially available.

[0044] Hydrosilylation catalyst (B2a3) The hydrosilylation catalyst (B2a3) is preferably a platinum group metal (platinum, ruthenium, osmium, rhodium, iridium, and palladium) or a compound thereof. Platinum and / or platinum compounds are preferred, such as finely divided platinum; chloroplatinic acid or an alcoholic solution of chloroplatinic acid; olefin complexes of chloroplatinic acid; complexes of chloroplatinic acid with alkenylsiloxanes; platinum-diketone complexes; metallic platinum on silica, alumina, carbon, or a similar support; or thermoplastic resin powders containing platinum compounds. Catalysts based on other platinum group metals can be exemplified by rhodium, ruthenium, iridium, or palladium compounds. For example, these catalysts can be represented by the following formulas: RhCl(PPh3)3, RhCl(CO)(PPh3)2, Ru3(CO) 12 , IrCl(CO)(PPh3)2, and Pd(PPh3)4 (where Ph represents a phenyl group).

[0045] The catalyst (B2a3) is preferably used in an amount of 0.5 to 100 ppmw of platinum group metal, more preferably 1 to 50 ppm, based on the polyorganosiloxane composition (B). The hydrosilylation catalyst (B2a3) catalyzes the reaction of alkenyl groups of the diorganopolysiloxane polymer (B2a1) with Si-H groups of (B2a2).

[0046] Inhibitor (B2a5) Optionally, when a hydrosilylation catalyst is utilized to cure the diorganopolysiloxane polymer (B2a1), an inhibitor (B2a5) may be included in the composition to slow the curing process. The term "inhibitor" as used herein means a material that, when incorporated in small amounts, such as less than 10 weight percent of the silicone composition (B2a1), slows the curing of component (B2a1) without preventing the cure of the mixture as a whole.

[0047] Inhibitors for platinum group based catalysts (B2a5), especially platinum based catalysts (B2a5), are well known and include hydrazines, triazoles, phosphines, mercaptans, organic nitrogen compounds, acetylenic alcohols, silylated acetylenic alcohols, maleates, fumarates, ethylenically or aromatic unsaturated amides, ethylenically unsaturated isocyanates, olefinic siloxanes, unsaturated hydrocarbon mono- and diesters, conjugated ene-ynes, hydroperoxides, nitriles, and diaziridines.

[0048] The inhibitor (B2a5) used herein, when present, may be selected from the group consisting of acetylenic alcohols and their derivatives containing at least one unsaturated bond. Examples of acetylenic alcohols and their derivatives include 1-ethynyl-1-cyclohexanol (ETCH), 2-methyl-3-butyn-2-ol, 3-butyn-1-ol, 3-butyn-2-ol, propargyl alcohol, 2-phenyl-2-propyn-1-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclopentanol, 1-phenyl-2-propynol, 3-methyl-1-penten-4-yn-3-ol, and mixtures thereof.

[0049] Alternatively, the inhibitor (B2a5) is selected from the group consisting of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butyn-2-ol, 3-butyn-1-ol, 3-butyn-2-ol, propargyl alcohol, 2-phenyl-2-propyn-1-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclopentanol, 1-phenyl-2-propynol, and mixtures thereof.

[0050] The inhibitor (B2a5) may typically be an acetylenic alcohol with at least one unsaturated bond (alkenyl group) in a terminal position and optionally a methyl or phenyl group in the alpha position. The inhibitor may be selected from the group consisting of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butyn-2-ol, 3-butyn-1-ol, 3-butyn-2-ol, propargyl alcohol, 2-phenyl-2-propyn-1-ol, 1-phenyl-2-propynol, and mixtures thereof.

[0051] The inhibitor (B2a5) may be added in the range of 0-10% by weight of component (B), or 0.05-5% by weight of component (B2), but is typically used in an amount sufficient to retard the cure of the diorganopolysiloxane gum (B2a1), which amount can be optimized for a given system by one of ordinary skill in the art using routine experimentation.

[0052] Radical initiator (B2a4) The radical initiator (B2a4) is a compound that decomposes at high temperature to form radical species. The latter promotes the crosslinking reaction between the alkenyl groups of the diorganopolysiloxane gum (B2a1) during the dynamic vulcanization step of the process. This component can be exemplified by known azo compounds, carbon compounds, and organic peroxy compounds, such as hydroperoxides, diacyl peroxides, ketone peroxides, peroxyesters, dialkyl peroxides, diaryl peroxides, aryl-alkyl peroxides, peroxydicarbonates, peroxyketals, peroxyacids, acyl alkylsulfonyl peroxides, and alkyl monoperoxydicarbonates.

[0053] For the purposes of the present invention, the radical initiator (B2a4) is selected such that the difference between the 6 minute half-life temperature of the initiator and the process temperature is between -60°C and 20°C. That is, the following condition is met: -60°C < {T(6) - T(O)} < 20°C, where T(6) represents the temperature (°C) at which the initiator has a half-life of 6 minutes, and T(O) represents the processing temperature (°C) before the initiator is added (i.e., the actual temperature of the mixture of components (B1) to (B3)). The value of T(6) is available from the initiator manufacturer or can be determined by methods known in the art. After the initiator is introduced, the temperature usually rises slightly as dynamic vulcanization occurs unless cooling is intentionally performed. However, such cooling is usually not required unless the temperature increases dramatically (e.g., above about 30°C).

[0054] Specific non-limiting examples of suitable radical initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), dibenzoyl peroxide, tert-amyl peroxyacetate, 1,4-di(2-tert-butylperoxyisopropyl)benzene, tert-butylcumyl peroxide, 2,4,4-trimethylpentyl-2 hydroperoxide, diisopropylbenzene monohydroperoxide, cumyl hydroperoxide, tert-butyl hydroperoxide, tert-amyl hydroperoxide, 1, Examples of peroxyalkylene compounds include 1-di(tert-butylperoxy)cyclohexane, tert-butylperoxyisopropyl carbonate, tert-amyl peroxybenzoate, dicumyl peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexanebis(1-methyl-1-phenylethyl)peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, di-tert-butyl peroxide, α,α-dimethylbenzyl hydroperoxide, and 3,4-dimethyl-3,4-diphenylhexane.

[0055] The initiator (B2a4) is used in an amount sufficient to cure the diorganopolysiloxane gum (B2a1), which amount can be optimized for a given system by one skilled in the art using routine experimentation. If the amount is too low, insufficient crosslinking occurs, resulting in poor mechanical properties. This is easily determined by performing a few simple experiments for the system under consideration. On the other hand, adding too much initiator is uneconomical and tends to cause undesirable side reactions, such as polymer decomposition. The initiator (B2a4) is preferably added at a level of 0.05 to 6 parts by weight, or alternatively 0.2 to 3 parts by weight, per 100 parts by weight of diorganopolysiloxane (B2a1).

[0056] Diorganopolysiloxane (B2b1) The diorganopolysiloxane (B2b1) has a viscosity of at least 100,000 mm at 25°C. 2 ·s -1 (cSt), or at least 1,000,000 mm at 25°C 2 ·s -1 (cSt) of viscosity. The silicon-bonded organic groups of component (B2b1) are independently selected from the hydrocarbon or halogenated hydrocarbon groups defined in (B2a1) above. Again, methyl preferably constitutes at least 85 mole percent, more preferably at least 90 mole percent, of the silicon-bonded organic groups in component (B2b1).

[0057] Thus, the polydiorganosiloxane (B2b1) may be a homopolymer, copolymer, or terpolymer containing such organic groups. Examples include fluids or gums that contain, in particular, dimethylsiloxy and phenylmethylsiloxy units; dimethylsiloxy and diphenylsiloxy units; and dimethylsiloxy, diphenylsiloxy, and phenylmethylsiloxy units. The molecular structure is also not critical, and examples include linear and partially branched linear chains, although linear structures are preferred.

[0058] Specific examples of organopolysiloxanes (B2b1) include dimethylhydridosiloxy end-capped dimethylsiloxane homopolymers, dimethylhydroxysiloxy end-capped methylphenylsiloxane-dimethylsiloxane copolymers, and dimethylhydroxysiloxy end-capped methylphenylpolysiloxanes. Preferred systems for low temperature applications include silanol-functional methylphenylsiloxane-dimethylsiloxane copolymers and diphenylsiloxane-dimethylsiloxane copolymers, particularly those in which the molar content of dimethylsiloxane units is about 93%.

[0059] Component (B2b1) may also consist of a combination of two or more organopolysiloxane fluids or gums. Most preferably, component (B2b1) is a polydimethylsiloxane homopolymer terminated with silanol groups at each end of the molecule.

[0060] Preferably, the molecular weight of the diorganopolysiloxane is sufficient to impart a Williams plasticity, as determined by ASTM D-926-08, of at least about 30. As used herein, plasticity is the plasticity measured by the measurement of the plasticity of a specimen after it has been subjected to a compressive load of 49 Newtons at 25° C. for 3 minutes, in a volume of 2 cm. 3 , defined as the thickness in millimeters times 100 for a cylindrical specimen of height about 10 mm. Although there is no absolute upper limit to the plasticity of component (B2b1), practical considerations of processability in conventional mixing equipment usually limit this value. Preferably, the plasticity should be about 100-200, most preferably about 120-185. The inventors have found that such gums can be easily dispersed in one or more thermoplastic organic materials (B1) without the need for a filler (B2c).

[0061] However, it has been found that fluid diorganopolysiloxanes having viscosities of about 10-100 Pa-s at 25° C. often cannot be readily dispersed in the thermoplastic resin (A). Under these circumstances, the fluid must be mixed with up to about 300 parts by weight of a filler (B2c), described below, for every 100 parts by weight of (B2b1) to facilitate dispersion. Preferably, the fluid and filler are mixed before the combination is added to the resin (A), although they may be added separately.

[0062] Condensation catalyst (B2b3) Typically, the condensation catalyst (B2b3) of the present invention is any compound that promotes the condensation reaction between the Si-OH groups of the diorganopolysiloxane (B2b1) and the Si-H groups of the organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, thereby curing the former by forming --Si--O--Si-- bonds. However, as mentioned above, the catalyst (B2b3) cannot be a platinum compound or complex, since the use of such condensation catalysts often leads not only to insufficient processing, but also to insufficient physical properties of the resulting TPSiV.

[0063] The condensation catalyst (B2b3) is present in an amount sufficient to cure the diorganopolysiloxane (B2b1) and the organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule (B2a2), as defined above.

[0064] Examples of suitable catalysts include metal carboxylates such as dibutyltin diacetate, dibutyltin dilaurate, tripropyltin acetate, stannous octoate, stannous oxalate, stannous naphthalate, and the like; amines such as triethylamine, ethylenetriamine, and the like; and quaternary ammonium compounds such as benzyltrimethylammonium hydroxide, beta-hydroxyethyltrimethylammonium-2-ethylhexoate, and beta-hydroxyethylbenzyltrimethyldimethylammonium butoxide (see, e.g., U.S. Pat. No. 3,024,210).

[0065] Optional reinforcing filler (B2c). Optionally, the composition used to prepare the silicone elastomer may contain a reinforcing filler (B2c). The reinforcing filler (B2c) may be, for example, silica. The silica may be, for example, a fumed (pyrolytic) silica, such as that sold by Cabot under the trademark Cab-O-Sil MS-75D, or may be a precipitated silica. The particle size of the silica may range, for example, from 0.5 μm to 20 μm, or alternatively from 1 μm to 10 μm. The silica may be, for example, a treated silica, prepared by treating silica with a silane or polysiloxane. The silane or polysiloxane used to treat the silica typically contains hydrophilic groups attached to the silica surface, as well as aliphatically unsaturated hydrocarbon or hydrocarbon oxy groups and / or hydrogen atoms attached to Si.

[0066] Silica can be treated with, for example, an alkoxysilane, such as a silane containing at least one alkoxy group bonded to Si and at least one alkenyl group bonded to Si or at least one hydrogen atom bonded to Si. The alkoxysilane can be a monoalkoxysilane, dialkoxysilane, or trialkoxysilane containing at least one aliphatically unsaturated hydrocarbon group (e.g., vinylalkoxysilanes such as vinyltrimethoxysilane, vinyltriethoxysilane, or vinylmethyldimethoxysilane). The alkoxy group bonded to Si can be easily hydrolyzed to a silanol group that is bonded to the silica surface.

[0067] Alternatively, the silica can be treated with a polysiloxane, such as an oligomeric organopolysiloxane, containing Si-bonded alkenyl groups and silanol end groups.

[0068] The silica can be treated, for example, with 2% to 60% by weight, based on the silica, of an alkenyl-containing alkoxysilane or an alkenyl-containing oligomeric organopolysiloxane.

[0069] Thermoplastic organic material (A) The above-mentioned master batch is prepared and then placed in the thermoplastic material (A). As with the thermoplastic organic material (B1), the thermoplastic material (A) may be polycarbonate (PC); blends of polycarbonate with other polymers, such as polycarbonate-acrylonitrile-butadiene-styrene (PC / ABS) blends and polycarbonate-polybutylene terephthalate (PC / PBT) blends; polycaprolactam (nylon-6), polylauryllactam (nylon-12), polyhexamethylene adipamide (nylon-6,6), polyhexamethylene dodecane amide (nylon-6,12). Polyamides, exemplified by nylons such as poly(hexamethylene sebacamide) (nylon 6,10), and blends of nylon with other polymers; polyesters, exemplified by polybutylene terephthalate (PBT), polyethylene terephthalate (PET), and polyethylene naphthalate (PEN); polyphenylene ether (PPE), polyphenylene oxide (PPO), and blends of PPE or PPO with styrenic resins, such as high impact polystyrene (HIPS), polystyrene, acrylonitrile-butadiene-styrene (ABS), and blends with styrene-acrylonitrile resins (SAN), etc.; styrenic materials exemplified by polyphenylene sulfide (PPS), polyethersulfone (PES), polyaramids, polyimides, phenyl-containing resins with rigid rod structures, ABS (acrylonitrile-butadiene-styrene), polystyrene (PS), and HIPS; polyacrylates; halogenated plastics exemplified by polyvinyl chloride, fluoroplastics, and any other halogenated plastic; polyketones; polymethyl methacrylate (PMMA); polyolefins exemplified by polypropylene (PP), polyethylene (PE) (including high density polyethylene (HDPE) and low density polyethylene (LDPE)), polybutene (PB), and copolymers and blends of polyolefins; thermoplastic elastomers such as thermoplastic urethanes, thermoplastic polyolefin-based elastomers, thermoplastic vulcanizates; styrene-ethylene-butylene-styrene (SEBS) copolymers; and natural products such as cellulose, rayon, and polylactic acid.As indicated above, the one or more thermoplastic organic materials (B1) may be a mixture of two or more of the thermoplastic resins mentioned above.

[0070] Linear organopolysiloxane (B3) The linear organopolysiloxane (B3) has a viscosity of at least 10,000 mm at 25° C., typically measured using a Brookfield viscometer and a spindle most appropriate for the viscosity range being measured. 2 ·s -1 (cSt), or at least 50,000 mm at 25°C 2 ·s -1 , or at least 500,000 mm at 25°C 2 ·s -1 , or 600,000 mm 2 ·s -1 The silicone-bonded organic groups of component (B3) may be a fluid or gum having a viscosity of 1000 psi (cSt) or greater. The silicon-bonded organic groups of component (B3) are independently selected from hydrocarbon or halogenated hydrocarbon groups. These may be specifically exemplified by alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, and hexyl; cycloalkyl groups, such as cyclohexyl and cycloheptyl; alkenyl groups having 2 to 20 carbon atoms, such as vinyl, allyl, and hexenyl; aryl groups having 6 to 12 carbon atoms, such as phenyl, tolyl, and xylyl; aralkyl groups having 7 to 20 carbon atoms, such as benzyl and phenethyl; and halogenated alkyl groups having 1 to 20 carbon atoms, such as 3,3,3-trifluoropropyl and chloromethyl. Of course, it will be understood that these groups are selected such that the diorganopolysiloxane has a glass transition temperature (or melting point) below room temperature, such that the component forms an elastomer when cured. At least 85 mole percent, and more preferably at least 90 mole percent, of the silicon-bonded organic groups in component (B3) are methyl and / or ethyl groups, alternatively methyl groups.

[0071] Thus, polydiorganosiloxane (B3) may be a homopolymer, copolymer, or terpolymer containing such organic groups. Examples include fluids or gums that contain, in particular, dimethylsiloxy and phenylmethylsiloxy units; dimethylsiloxy and diphenylsiloxy units; and dimethylsiloxy, diphenylsiloxy, and phenylmethylsiloxy units. The molecular structure is also not critical, and examples include linear and partially branched linear, although linear structures are preferred.

[0072] Stabilizer (C) The compositions herein may also include a stabilizer (C). The stabilizer (C) may be an antioxidant, for example a hindered phenol antioxidant such as tetrakis(methylene(3,5-di-tert-butyl-4-hydroxy-hydrocinnamate)methane sold by BASF as Irganox® 1010'. Such antioxidants may be used, for example, at 0.05 to 0.5 weight percent of the thermoplastic composition.

[0073] Other optional additives (Component (D)) Other optional additives (component (D)) may be added to the aforementioned thermoplastic compositions to obtain desired processing or performance properties and / or to enhance compatibility between the silicone phase (B) and the thermoplastic matrix (A). These additives may be added, for example, to the silicone-based composition if they are required to be present in the silicone elastomer, or they may be added directly to the thermoplastic matrix if the additive is intended to be present in the thermoplastic matrix.

[0074] Such additional components include, for example, softening mineral oils, plasticizers, other inorganic fillers (i.e. excluding (B2c) reinforcing fillers), viscosity modifiers, lubricants, coupling agents, thermoplastic elastomers, and fire-resistant additives; colorants such as pigments and / or dyes; effect pigments such as diffractive pigments; interference pigments such as pearlescent agents; reflective pigments, and mixtures thereof as well as mixtures of any of the above-mentioned pigments; UV stabilizers, flow agents, anti-wear agents, mold release agents, plasticizers, impact modifiers, surfactants, gloss agents, fillers, fibers, waxes, and mixtures thereof, and / or any other additives not listed in (C) that are well known in the art of polymers.

[0075] Mineral oils are usually 15 ~C 40 The mineral oil may be a petroleum fraction in the range of, for example, white oil, liquid paraffin, or naphthenic oil. If used, the mineral oil may be premixed with, for example, the thermoplastic organic polymer (A). The mineral oil may be present, for example, in an amount of 0.5 to 20% by weight based on the thermoplastic organic polymer (A). The plasticizer may be present in combination with or in place of the mineral oil. Examples of suitable plasticizers include isopropylated triaryl rephosphate, resorcinal bis-(diphenyl phosphate), or phosphate ester plasticizers such as the phosphate ester sold under the trademark Reofos® RDP by Great Lakes Chemical Corporation. Such plasticizers may be used, for example, in the range of 0.5% to 15% by weight of the composition.

[0076] The coupling agent is selected from a glycidyl ester functional polymer, an organofunctional graft polymer, an organofunctional modified organopolysiloxane, a polymer composition including a thermoplastic polymer selected from polar and non-polar polymers and a branched block copolymer of a polysiloxane and a polymer, or a mixture thereof.

[0077] Examples of other inorganic fillers include talc or calcium carbonate. The fillers may be treated to render their surface hydrophobic. Such fillers, if present, are preferably present in lower amounts than the reinforcing fillers (B2c), such as silica. The fillers may be premixed either with the thermoplastic organic polymer (A) or with the silicone base (B1).

[0078] Examples of pigments include carbon black and titanium dioxide. The pigment may, for example, be premixed with the thermoplastic organic polymer (A). The lubricant may be, for example, an external lubricant additive to improve the processability of the thermoplastic material in molding operations. An example of an external lubricant additive is ethyl butyl stearamide sold by CRODA under the trademark "Crodamide-EBS". The lubricant may be present, for example, in an amount of 0.1 to 2 weight percent of the thermoplastic elastomer composition.

[0079] The use of flame retardant additives to impart flame retardant properties to the compositions of the present invention is also considered within the scope of the present invention. Conventional flame retardants may be used herein and may be selected from the group consisting of halogenated species such as polydibromostyrene, copolymers of dibromostyrene, polybromostyrene, brominated polystyrene, tetrabromophthalate esters, tetrabromophthalate diol, tetrabromophthalate anhydride, tetrabromobenzoate esters, hexabromocyclododecane, tetrabromobisphenol A, tetrabromobisphenol A bis(2,3-dibromopropyl ether), tetrabromobisphenol A bis(allyl ether), phenoxy terminated carbonate oligomers of tetrabromobisphenol A, decabromodiphenylethane, decabromodiphenyl oxide, bis-(tribromophenoxy)ethane, ethane-1,2-bis(pentabromophenyl), tetradecabromodiphenoxybenzene, ethylene bistetrabromophthalimide, ammonium bromide, polypentabromobenzyl acrylate, brominated epoxy polymers, brominated epoxy oligomers, and brominated epoxies. Other non-halogen species can be selected from materials such as isopropylated triaryl phosphate, cresyl diphenyl phosphate, tricresyl phosphate, trixylyl phosphate, triphenyl phosphate, butylated triaryl phosphate, resorcinol bis-(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), melamine phosphate, melamine pyrophosphate, melamine polyphosphate, dimelamine phosphate, melamine, melamine cyanurate, magnesium hydroxide, antimony trioxide, red phosphorus, zinc borate, and zinc stannate.

[0080] A single optional additive or multiple optional additives (component (D)) may be used in the thermoplastic masterbatch composition. The total proportion of the one or more additives of component (D) present should not exceed 30 wt.% of the total weight of the thermoplastic masterbatch composition. Preferably, when one or more components (D) are present, the total cumulative amount of said additives typically accounts for 0.01-20 wt.%, preferably 0.01-10 wt.%, preferably 0.01-5 wt.% of the total weight of the masterbatch composition B.

[0081] Also provided is a method for producing a molded article using the thermoplastic composition described above, the method comprising: (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch (B) containing (i) mixing the components used to make the silicone elastomer (B2) to form a silicone composition; (ii) blending the silicone composition with one or more thermoplastic organic materials; (iii) dynamically vulcanizing the silicone composition to form a silicone elastomer (B2) in the preparation of the silicone elastomer B2; and / or (iv) introducing (B3) during step (ii) or after step (iii) when B2 is present; The method comprises the steps of: The masterbatch (B) contains 20 to 60% by weight of a crosslinked silicone elastomer, based on the weight of (B1)+(B2)+(B3); blending the resulting masterbatch with one or more thermoplastic organic materials (A) in an amount such that the thermoplastic elastomer composition contains a total of 0.2 to 25 weight percent crosslinked silicone elastomer, based on the weight of (A)+(B); and molding a thermoplastic material to form a molded article; The thermoplastic material may be a thermoplastic elastomer material.

[0082] In another embodiment, the method of making a thermoplastic material, which may be a thermoplastic elastomer material, comprises making a masterbatch (B) as described above and blending the resulting masterbatch with one or more thermoplastic organic materials (A) in an amount such that the thermoplastic material contains a total of 0.2 to 25 weight percent crosslinked silicone elastomer, based on the weight of (A)+(B). In one alternative, the masterbatch is placed in component (A) in pellet form. In another alternative, both components (A) and (B) are dry blended together in pellet form.

[0083] For the above described method, several alternatives may be used.

[0084] The plastics processing step and the equipment for blending components B1, B2, and optional B3, and the blending of components (A) and (B) for the production of thermoplastic materials utilizing the need to soften the thermoplastic resins (A) and (B1) when heated, and the contacting and uniform mixing of the components, can be carried out at temperatures ranging from 60°C to 400°C, depending on the softening or melting temperature of the thermoplastic resin. Convenient equipment for any such process can be exemplified by, but not limited to, extrusion kneading steps utilizing single screw extruders, twin screw extruders, or multi-screw extruders. Alternatively, the blending can be carried out using, for example, a batch-type internal mixer such as a Z-blade mixer, or a Banbury mixer, where sufficient mixing time is provided to ensure that the components are uniformly distributed.

[0085] Below is presented a selection of alternative processes that can be utilized to prepare the masterbatches and thermoplastic elastomer compositions described hereinabove.

[0086] Masterbatches can be prepared using the following process, in which the successive incorporation steps may be in the order shown, but alternatively the steps may be in another order, and in some cases some steps may be combined where appropriate depending on the layout of the processing equipment and the feed composition: 1. One or more thermoplastic organic materials (B1) are first softened or melted, if desired, at a temperature of from 60°C to 400°C. 2. The components of (B2) that participate in the dynamic vulcanization of the diorganopolysiloxane gums (B2a1) or (B2b1) form the silicone elastomer portion of the masterbatch composition, which is then placed into one or more thermoplastic organic materials (B1) at elevated temperature.

[0087] The silicone elastomer (B2) is then prepared by dynamically curing one of the following curing compositions, which may optionally additionally comprise one or more of (B2c), (B3), (C), and / or (D): 1) (B2a1) a diorganopolysiloxane having an average of at least two alkenyl groups per molecule, and an organopolysiloxane having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule (B2a2), and a hydrosilylation catalyst (B2a3), and optionally a catalyst inhibitor (B2a5); 2) (B2a1) a diorganopolysiloxane having an average of at least two alkenyl groups per molecule, and a radical initiator (B2a4), and optionally an organopolysiloxane having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule (B2a2); or 3) silanol-terminated diorganopolysiloxanes (B2b1), an organopolysiloxane (B2b2) having at least two Si-bonded hydrogen atoms, containing on average at least two Si-bonded hydrogen groups; and Condensation catalyst (B2b3).

[0088] The diorganopolysiloxane gum (B2a1) or (B2b1) is introduced and distributed into the softened or molten matrix of one or more thermoplastic organic materials (B1) under mechanical mixing energy.

[0089] The components of the alternative cure packages are then introduced into the mixture separately (without any preferred order) or in distributed combination to initiate and complete the vulcanization of each gum. As previously mentioned, in the case of the hydrosilylation (addition) cure process, a hydrosilylation (addition cure) reaction inhibitor (B2a5) may optionally be placed in the mixture to increase the residence time before the vulcanization reaction is completed. If utilized, the inhibitor (B2a5) is placed in the composition before either the catalyst and / or the crosslinker.

[0090] The optional additives (B2c), (B3), (C), and / or (D) may be added simultaneously or separately during or after the dynamic curing process, as needed. A reinforcing filler for the diorganopolysiloxane (B2c) may be added separately. For example, the stabilizer (C) and additional component (D) may be pre-blended with the one or more thermoplastic organic materials (B1) in solid form before (B1) is exposed to high temperatures, or may be added to the one or more thermoplastic organic materials (B1) in the melt during the mixing step.

[0091] Alternatively, the predispersed organopolysiloxane composition may be incorporated into one or more thermoplastic organic materials (B1) at elevated temperatures, rather than each component being incorporated separately as described above. The predispersed organopolysiloxane composition may comprise a single mixture of all components used in the preparation of the silicone elastomer, or the incorporation of a mixture of two or more components that, when mixed together, complete the components required for the dynamic vulcanization of (B2a1) or (B2b1) to form the silicone elastomer may be utilized. The use of predispersed organopolysiloxane compounds may complement or replace the incorporation of individual components.

[0092] The predispersed organosiloxane composition may comprise a diorganopolysiloxane having reactive groups, or a blend of diorganopolysiloxanes having reactive groups, i.e. (B2a1) or (B2b1), comprising either a reinforcing filler (B2c) or a crosslinker (e.g. (B2a2) or (B2b2)) or a combination of a reinforcing filler (B2c) and a crosslinker (e.g. (B2a2) or (B2b2)). The components of the predispersed organosiloxane compound composition are blended together before being placed into one or more thermoplastic organic materials (B1). The other components can then be placed independently.

[0093] Alternatively, there may be two pre-dispersed compositions (i.e. a two-component composition) mixed together in the heated thermoplastic organic material or materials (B1): 1. a first component comprising an organopolysiloxane (B2a1 or B2b1) and a hydrosilylation catalyst (B2a3) or a condensation catalyst (B2b3); 2. A second component comprising an organopolysiloxane (B2a1) or (B2b1), an organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, and an optional reaction inhibitor (B2a5).

[0094] In another alternative, one or more components for producing silicone elastomers may be incorporated into one or more thermoplastic organic materials (B1) in the form of a pre-prepared masterbatch or liquid concentrate. For example, a suitable crosslinker may be incorporated into the composition to blend a thermoplastic material, such as a linear organopolysiloxane concentrate or the same material as the siloxane masterbatch, into the masterbatch. Similarly, if present, siloxane (B3) may be incorporated in the form of a masterbatch prepared upstream by a separate mixing step.

[0095] In yet another alternative, the need for dynamic vulcanization of the one or more thermoplastic organic materials (B1) can be avoided by premixing and curing the components of the composition used to make the silicone elastomer, thereby blending the cured silicone elastomer into the one or more thermoplastic organic materials (B1).

[0096] The silicone elastomer concentrate may be incorporated into the final composition at elevated temperature into one or more molten thermoplastic organic materials (B1) or may be pre-blended with one or more thermoplastic organic materials (B1) in solid form before the blend is placed into the processing equipment and exposed to elevated temperatures.

[0097] In a further alternative, the masterbatch of (B3) (if required) and the masterbatch(s) of the components for producing the silicone elastomer (B2) may all be pre-prepared and then placed at high temperature into one or more thermoplastic organic materials (B1) and appropriately mixed together.

[0098] An example of a suitable melt blending device is a twin screw extruder. Twin screw extruders with a length / diameter (L / D) ratio of more than 40 may be particularly suitable. The thermoplastic organic polymer (A) may be introduced, for example, into the main feed of a co-rotating twin screw extruder operated at a temperature high enough to melt the thermoplastic organic polymer. The organopolysiloxane (B) may be added, for example, using a gear pump, into the already molten thermoplastic organic polymer phase. The residence time of the liquid phase reagents in the extruder may be, for example, from 30 to 240 seconds, optionally from 50 to 150 seconds.

[0099] The assembly as previously described herein comprises: The molded article includes a molded article in frictional contact with a sliding member, the molded article and the sliding member being configured to move relative to one another while remaining in contact, the molded article including: (A) one or more thermoplastic organic materials; (B) (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier comprising The thermoplastic material includes a blend of The masterbatch (B) contains 20-60% by weight of crosslinked silicone elastomer based on the weight of (B1)+(B2)+(B3), and the thermoplastic elastomer composition contains a total of 0.05-25% by weight of crosslinked silicone elastomer based on the weight of (A)+(B). The thermoplastic material may be a thermoplastic elastomer material.

[0100] In one embodiment, both the molded article and the sliding member are (A) one or more thermoplastic organic materials; (B) (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier comprising made from a thermoplastic material, such as a thermoplastic elastomeric material, including a blend of The masterbatch (B) contains 20-60% by weight of crosslinked silicone elastomer, based on the weight of (B1)+(B2)+(B3), and the thermoplastic material contains a total of 0.05-25% by weight of crosslinked silicone elastomer, based on the weight of (A)+(B).

[0101] The molded article described herein above may be any article designed to maintain frictional contact with a second object, referred to herein as a sliding member, while moving in frictional contact with said sliding member in use. Typically, the molded article and the sliding member move in frictional contact with each other. However, it should be understood that one of them may be stationary while the other is moving, or both may be moving simultaneously, but in each case they may slide relative to each other in motion (i.e. in frictional contact) and therefore need to overcome relative motion friction, resulting in stick-slip phenomena. Thus, the molded article may be, for example, an automotive part such as a housing, latch, window opening mechanism, wiper part, sunroof part, lever, bushing, gear, gearbox part, pivot housing, bracket, zipper, switch, cam, sliding element or plate, and in each case may be made from a thermoplastic composition or a thermoplastic elastomer composition. The sliding member may be any of the above, or a housing for the molded article and the sliding member to move relative to each other in use while maintaining frictional contact during use. The sliding members may be automotive parts such as housings, latches, window opening mechanisms, wiper parts, sunroof parts, levers, bushes, gears, gearbox parts, pivot housings, brackets, zippers, switches, cams, sliding elements, or plates that are in frictional contact with them. The moldings and sliding members may be parts of door panels, decorative trim, armrests, center consoles, dashboards, glove boxes, seats, for example, that are in frictional contact with them. Either or both of the moldings and sliding members may be manufactured by injection molding.

[0102] The sliding member may or may not be made of a thermoplastic or thermoplastic material. If the sliding member is made of a thermoplastic or thermoplastic elastomer material, said material may be the same as the material for manufacturing the moulded article. Alternatively, the sliding member may be made of a non-plastic material such as metal or leather.

[0103] The above-mentioned assembly may consist of a molded part and a sliding member. However, the molded part and the sliding member may instead form parts of a multi-part assembly, or the molded part and the sliding member may be parts that move in frictional contact with each other in the form of internal parts of the assembly. For example, the molded part and the sliding member may be connected together by a fastening mechanism such as nuts and bolts or screws, or may be clipped together. For example, a part of the molded part may be designed to be received (clipped) into the receiver of the sliding member, or vice versa.

[0104] It should be understood that by frictional contact, the molded articles and sliding members undergo frictional movement relative to one another that is required to overcome the dynamic friction forces to continue the movement during their functional life (and the functional life of the assembly). Historically, the molded articles and sliding members routinely succumbed to stick-slip phenomena and associated noises (e.g., squealing, etc.), but the presence of the masterbatch ingredients described above allows the molded articles and sliding members to move relative to one another with significantly reduced occurrence of stick-slip phenomena and associated noises.

[0105] Thus, for example, an assembly is typically made of a thermoplastic sliding member made by injection molding from a first thermoplastic material not modified with the masterbatch and its molded part made from a second thermoplastic material incorporating the masterbatch, clipped together or assembled with the molded part and the sliding member in frictional contact, and the occurrence of squeaking noise and stick-slip phenomenon is significantly reduced or completely avoided. The invention allows for an effective replacement of traditional anti-squeak coatings, external greases, and felts, manufacturing flexibility, improved wear resistance, use during compounding or injection molding, reduced design costs, and excellent surface finish. The invention is particularly well suited for PC / ABS blends. EXAMPLES

[0106] The invention is illustrated by the following examples in which parts and percentages are by weight unless otherwise stated.

[0107] Silicone rubber masterbatches were prepared using the materials listed and the amounts of two silicone rubber bases shown in Table 1 below. i) Si Rubber Base 1 is an uncatalyzed silicone rubber base with a Shore A hardness of 70 (measured according to ASTM D2240-03) containing a blend of organopolysiloxane gum and silica filler. The gum blend is a mixture of vinyl dimethyl terminated polydimethylsiloxane, vinyl dimethyl terminated polydimethylmethylvinylsiloxane copolymer gum, and trimethyl terminated polydimethylmethylvinylsiloxane copolymer. The specific gravity of the gum is 1.23 and the Williams plasticity of the gum blend measured according to ASTM D-926-08 is comprised between 300 and 450 mm / 100. ii) The silica used as reinforcing filler is a fumed (pyrogenic) silica having a particle size comprised between 0.5 μm and 20 μm, such as that sold by Cabot under the trademark Cab-O-Sil MS-75D. The silica is pretreated with an oligomeric organopolysiloxane containing vinylmethylsiloxane units and silanol end groups. iii) Si Rubber Base 2 is an uncatalyzed silicone rubber base having a Shore A hardness of 40 (measured according to ASTM D2240-03) containing a blend of organopolysiloxane gum and silica filler. The gum blend is a mixture of vinyldimethyl terminated polydimethylsiloxane, vinyldimethyl terminated polydimethylmethylvinylsiloxane copolymer gum, and trimethyl terminated polydimethylmethylvinylsiloxane copolymer. The specific gravity of the gum is 1.11 and the Williams plasticity of the blend measured according to ASTM D-926-08 is comprised between 150 and 200 mm / 100. iv) The silica used as reinforcing filler is a fumed (pyrogenic) silica having a particle size comprised between 0.5 μm and 20 μm, such as that sold by Cabot under the trademark Cab-O-Sil® MS-75D, which is pretreated with an oligomeric organopolysiloxane containing vinylmethylsiloxane units and silanol end groups. v) The platinum catalyst used in the examples was DowSil® Syl-Off® 4000 catalyst from the Dow Chemical Company, Midland Michigan. vi) The crosslinker used in the examples was DowSil® Syl-Off® 7678 crosslinker from the Dow Chemical Company, Midland Michigan. vii) The ethylene acrylate copolymer used was Elvaloy® AC1609 from Dupont, with a comonomer content of 9% by weight, an MFI of 6g / 10' (190°C / 2.16kg), a density of 0.93, a Vicat softening point of 70°C and a melting point of 101°C. viii) The antioxidant used was Irganox® 1010 from BASF, a sterically hindered phenolic antioxidant.

[0108] The compositions used are shown in Table 1.

[0109] [Table 1]

[0110] The mixing of the components and the silicone vulcanization reaction were carried out using a twin screw extruder with a diameter of 25 mm and a length of 48 L / D. The processing barrel section of the twin screw extruder was heated in the range of 160°C to 180°C (180°C to 200°C at the die). The ethylene acrylate copolymer was fed into the main inlet port of the extruder and melted as it passed through the extruder. Downstream, the silicone base, platinum catalyst, and Si-H crosslinker were separately introduced into the molten ethylene acrylate copolymer to ensure uniform dispersion of the silicone base and dynamic vulcanization reaction to form the silicone elastomer in the molten ethylene acrylate copolymer. The positions of the individual injection ports were set to ensure that the silicone vulcanization reaction was completed within the residence time of the ethylene acrylate copolymer in the extruder. In the case of the examples using uncured silicone base rubber, the platinum catalyst and the Si-H crosslinker were not introduced into the extruder. The resulting product was pelletized.

[0111] The resulting pelletized masterbatch product was dried at 110° C. for 2 hours to a maximum relative humidity of 0.02%.

[0112] The resulting silicone masterbatch in pellet form was then dry blended together in the required ratio with a thermoplastic blend of 70% by weight of polycarbonate (PC) and 30% by weight of acrylonitrile butadiene styrene (ABS) sold under the name Bayblend® T85XF by Covestro AG, Leverkusen, Germany, and kneaded by a melt mixing process using a co-rotating twin screw extruder characterized by D20 and L / D40. The processing temperature was set at 230-250°C, the screw speed was 200 rpm, and the throughput was 2.5 kg / h. The PC / ABS blend was also pre-dried at 110°C for 3 hours with a maximum relative humidity of 0.02% before being introduced into the extruder.

[0113] The above was compared to four comparison materials: COMP-1: Unmodified PC / ABS (30% ABS) - the material modified in the examples by the incorporation of the masterbatch described above. COMP-1 is used as a reference or baseline. The COMP-1 material was dried at 110°C for 3 hours prior to injection molding. COMP-2: Hushlloy® HS-210 - a commercial anti-squeak PC-ABS grade from Techno Polymer Co Limited. It is understood to be a chemically modified pre-formed PC / ABS based on copolymerization technology that imparts anti-stick-slip / anti-squeak behavior by imparting a greater "adhesive" behavior to prevent parts from moving relative to one another. COMP-3: Molykote® D96 UV Anti-Friction Coating, a fluorine-based UV-curable anti-squeak coating. This water-based coating contains 42% PTFE. This coating is a noise- and friction-resistant coating for the automotive industry (interior applications) that can be sprayed or brushed on. Perfluor-based coatings are best-in-class solutions for anti-squeak. The anti-squeak process is achieved by dramatically reducing the static and dynamic coefficients of friction of the coated parts against the corresponding parts. A plate of PC / ABS (30% by weight ABS) material was first cleaned with L-13 cleaner and then coated with a layer of the anti-friction coating about 20 μm thick. The plate was placed in an oven at 50° C. for 5 minutes and cured under UV. COMP-4: 2% by weight of PDMS added, with a dynamic viscosity of 1000mm at 25°C 2 ·s -1A trimethylsiloxy-terminated polydimethylsiloxane (PDMS) with a viscosity of 100 psi (cSt) (measured according to ASTM D445-17a) was prepared from the kneaded PC / ABS. The material was prepared by a twin screw extrusion process using liquid injection. Prior to injection molding, the material was dried at 110°C for 3 hours. PDMS is a well-known and very effective lubricant that has been used to minimize the squealing noise associated with some thermoplastic materials. However, it could be seen that the PDMS used was not very compatible with the PC / ABS thermoplastic material used in the examples - significant bleeding was observed after injection and the surface of the injection molded parts was not uniform, had a very oily feel and appearance, and lacked aesthetics. It was also noticed that the PDMS was not embedded in the host matrix and therefore washed away over time.

[0114] After preparation as described above, the example and comparative materials were injection molded. Typically, the injection temperature was 230-250°C and the pressure was 150 bar (15,000,000 Nm -2 ) back pressure, an injection speed of 0.35 m / s, and a mold temperature of 70° C. were used.

[0115] Stick-Slip / Squeak Rating: Squeak tests were performed on an SSP04 stick-slip test bench from Ziegler Instruments GmbH according to VDA230-206:2007 (Experiment on the stick-slip behavior of material pairs parts 1 to 3) in which a flat sample plate of the injection-molded example / comparative example under test (dimensions 100 x 100 x 4 mm) was slid across a flat rectangular piece of unmodified injection-molded PC / ABS (dimensions 25 x 50 mm) using the test parameters given in Table 2 below.

[0116] [Table 2]

[0117] The SSP04 Stick-Slip Test Bench provides several results from practical evaluations:- The Risk Priority Number or RPN gives a numerical value indicating the probability that a pair of materials will produce an audible squeaking noise according to VDA 230-206:2007 (ASTM 230-206). RPNs from 1 to 3 identify material pairs with no or minimal risk of squeaking. RPNs from 4 to 5 represent grades where no squeaking has been recorded but the material pair may develop squeaking in the long term. Finally, grades above 5, i.e. grades from 5 to 10, identify material pairs that produce an audible squeaking noise. The impulse value gives the number of stick-slips (start to finish) that occur between two surfaces during the test. Anti-squeak additives target lower impulse values. Maximum acceleration: The acceleration recorded during the restart phase of each stick-slip event. A high maximum acceleration results in the worst stick-slip event and a higher risk of noise generation. The static coefficient of friction (SCOF) is defined as the longitudinal force applied parallel to the displacement that produces motion. The kinetic coefficient of friction (DCOF) is defined as the longitudinal force required to keep one surface moving against another at a constant speed. The surface appearance of the test samples was rated by visual inspection as good (no visible evidence of product segregation or flow marks), poor (visible flow marks), or bloom (product segregation with surface flow marks and non-homogeneity). The Examples and Comparative Examples were also visually examined for evidence of surface wear (surface damage and scratches) after the Stick-Slip test, noting whether / when any audible noise was observed during the test procedure.

[0118] All results are expressed as the average of three independent samples that were subjected to 10 cycles (405 movements / cycle back and forth; 4050 movements in total). The unmodified PC / ABS underwent the same processing procedures (extrusion and injection molding) as the test samples to ensure that it underwent the same thermal history. The pre-prepared commercial PC / ABS, Comp3, was poured directly into the test mold. Compounded materials were prepared containing 4 wt% masterbatch or, in the case of Comp4, PDMS, as shown in Table 3 below.

[0119] The compounded formulations utilized in the testing are listed in Table 3 below:

[0120] [Table 3]

[0121] In the examples herein, Ex-1 and Ex-2 represent vulcanized silicone masterbatches, while Ex-3 and Ex-4 represent their non-vulcanized counterparts.

[0122] Test 1: This was done to demonstrate that the product from the present invention and designated as Ex-1 performs similarly under comparable conditions to current benchmark products and technical approaches exemplified by ComEx-2 and ComEx-3.

[0123] [Table 4]

[0124] As expected, the unmodified PC / ABS CompEx-1 had a very high RPN rating, the highest values ​​for both static and kinetic coefficient of friction (COF), and a high stick-slip occurrence frequency as indicated by an impulse value of 14,800 and a maximum acceleration of 6.4. The surface of the CompEx-1 sample during testing was found to have significant abrasion damage to the extent that polymer powder was present on the surface after testing due to surface abrasion. Finally, an audible noise was generated during testing.

[0125] The best-in-class benchmark, CompEx-3, shows excellent results. The coating imparts squeal-proof performance by producing a very low COF between the material pairs. The lowest static and dynamic COF results of 0.1 and 0.09 respectively were obtained, along with a very low RPN (average close to 1). The impulse rate was 516, which also contributed to the absence of noise generation along with a low maximum acceleration of 0.08.

[0126] CompEX-2 is a commercially available pre-formulated modified PC / ABS compound that gave excellent stick-slip performance without stick-slip occurrence. However, this compound showed a high COF value close to the original PC / ABS matrix. This may cause some problems in typical applications where good slip effect is required.

[0127] The results of Ex-1 compounding the thermoplastic silicone vulcanizate masterbatch into PC / ABS have an excellent RPN value of 1.2, which is comparable to CompEx-2 and CompEx-3 and well below the maximum allowable RPN value of 3. The aforementioned Ex-1 has performance values ​​comparable to CompEx-2 with slightly lower impulse and COF values, which in our opinion is more suitable than CompEx-2, whose results are closer to the aforementioned CompEx-3, which is considered best in class.

[0128] Experiment Part 2 A second series of tests was carried out looking at a wider range.

[0129] [Table 5]

[0130] Ex-1 and Ex-2 are crosslinked Si-MBs with high and low Shore A base gums, respectively. Ex-3 and Ex-4 are the corresponding non-crosslinked Si-MBs with high and low Shore A base gums. Interestingly, it was discovered that crosslinking is necessary for the high Shore A based gum Si-MBs to obtain anti-squeak performance. In fact, the non-crosslinked high Shore A silicone based Si-MB represented by Ex-3 did not show acceptable anti-squeak performance since an RPN of 4.3 was obtained along with higher impulse and maximum acceleration. Therefore, this Ex-3 does not meet the requirements of the present invention since it clearly showed an RPN number exceeding the limit of 3, which is the limit prescribed by VDA 230-206 to consider a material pair as anti-squeak.

[0131] In contrast, the low Shore silicone-based Si-MB, represented as Ex-2 and Ex-4, respectively, showed excellent anti-squeak performance with both cross-linked and non-cross-linked additives, although the surface appearance is dramatically improved by the cross-linking process, as Ex-2 showed excellent surface appearance while Ex-4 did not show good surface appearance.

[0132] As expected, Comp-Ex4 showed some anti-squeak performance with an average limit value of 2.8 RPN. The poor dispersion of PDMS and the non-uniformity of the surface are indicated by the high standard deviation measured in the RPN number and the low repeatability of the measurements. On the other hand, the surface was significantly affected by the blooming of PDMS during injection. The surface is very oily and lacks aesthetics, making it unsuitable for visible automotive applications. In addition, PDMS is difficult to use because it is a liquid. In this regard, Ex1, 2 and 4 from the present invention are easy to use (pellets) yet have excellent surface appearance and provide very good anti-squeak performance. The present application also relates to the following aspects: (1) (A) one or more thermoplastic organic materials; (B) (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier comprising A molded article of a thermoplastic material comprising a blend of A molded article, wherein the masterbatch (B) contains 20 to 60% by weight of components (B2) and (B3) based on the weight of (B1)+(B2)+(B3), and the thermoplastic elastomer composition contains 0.2 to 25% by weight of a crosslinked silicone elastomer based on the weight of (A)+(B). (2) The molded article according to (1) above, comprising component (B2) and optional component (B3). (3) The molded article according to (2) above, wherein the uncured organopolysiloxane (B3) is present in an amount of 0.1 to 25% by weight of the masterbatch (B). (4) Silicone elastomer (B2), if present, a diorganopolysiloxane (B2a1) containing an average of at least two alkenyl groups per molecule; (i) an organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, a hydrosilylation catalyst (B2a3), and an optional catalyst inhibitor (B2a5); or A radical initiator (B2a4); or Silanol-terminated diorganopolysiloxanes (B2b1), an organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, and Condensation catalyst (B2b3); The molded article according to any one of (1) to (3) above, which is prepared by dynamic vulcanization of any one of (1) to (3). (5) The molded article according to (4) above, wherein the diorganopolysiloxane (B2a1) or the diorganopolysiloxane (B2b1) is a gum having a Williams plasticity value of at least 100 mm / 100 as measured by ASTM D-926-08. (6) The molded article according to any one of (1) to (5), wherein the one or more thermoplastic organic materials (A) and (B1) may be the same or different and are selected from polycarbonate (PC); blends of polycarbonate with other polymers; polyamides and blends of polyamide with other polymers; polyesters; polyphenylene ether (PPE), polyphenylene oxide (PPO), and blends of PPE or PPO with styrene-based resins; polyphenylene sulfide (PPS), polyethersulfone (PES), polyaramids, polyimides, phenyl-containing resins having rigid rod structures, styrene-based materials; polyacrylates, SAN; halogenated plastics exemplified by polyketones, polymethyl methacrylate (PMMA), polyolefins, and copolymers and blends of polyolefins; thermoplastic elastomers such as thermoplastic urethanes, thermoplastic polyolefin-based elastomers, thermoplastic vulcanizates; styrene-ethylene-butylene-styrene (SEBS) copolymers; and natural products such as cellulose, rayon, and polylactic acid; and mixtures thereof. (7) The one or more thermoplastic organic materials (A) and (B1) are selected from the group consisting of polyester, polycarbonate, blends polycarbonate-acrylonitrile-butadiene-styrene (PC / ABS) blends, polycarbonate-polybutylene terephthalate (PC / PBT) blends, polycaprolactam (nylon-6), polylauryllactam (nylon-12), polyhexamethylene adipamide (nylon-6,6), polyhexamethylene dodecane amide (nylon-6,12), poly(hexamethylene sebacamide (nylon-6,10), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), and polyethylene naphthalate (PEN); polyphenylene ether (PPE), polyphenylene oxide (PPO), and mixtures of PPE or PPO with styrenic resins (high impact polystyrene (HIPS), polystyrene, acrylonitrile-butadiene). The molded article according to (6) above may be selected from diene-styrene-(ABS) and blends with styrene-acrylonitrile resin (SAN), etc.; polyphenylene sulfide (PPS), polyethersulfone (PES), polyaramid, polyimide, ABS (acrylonitrile-butadiene-styrene), polystyrene (PS) HIPS; polyacrylate, SAN; polyvinyl chloride, fluoroplastics, and any other halogenated plastics; polyketones; polymethyl methacrylate (PMMA), polypropylene (PP), polyethylene (PE), high density polyethylene (HDPE) and low density polyethylene (LDPE), polybutene (PB), and copolymers and blends of polyolefins, thermoplastic urethanes, thermoplastic polyolefin-based elastomers, thermoplastic vulcanizates; and styrene-ethylene-butylene-styrene (SEBS) copolymers. (8) The molded article according to (6) or (7), wherein the one or more thermoplastic organic materials (A) and (B1) may be selected from polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate, ABS (acrylonitrile-butadiene-styrene), polystyrene (PS), and high impact polystyrene (HIPS), polyacrylate, styrene-acrylonitrile resin (SAN), and any blend thereof. (9) The molded article according to any one of (1) to (8), which is an automobile part such as a housing, a latch, a window opening / closing mechanism, a wiper part, a sunroof part, a lever, a bush, a gear, a gearbox part, a pivot housing, a bracket, a zipper, a switch, a cam, a sliding element or a plate, and a door panel decorative trim, an armrest, a center console, a dashboard, a glove box, a seat part; and / or a combination of parts that come into frictional contact with a sliding member. (10) An assembly including a molded article according to any one of (1) to (8) that is in frictional contact with a sliding member, wherein the molded article and the sliding member are configured to move relative to each other while maintaining frictional contact. (11) The assembly according to (10) above, wherein the sliding member is the second molded product according to any one of (1) to (9) above. (12) The assembly according to (10) or (11), wherein the impulse member is made of a non-plastic material. (13) The assembly according to (10) or (11), wherein the assembly is a combination of parts in frictional contact including a door panel decorative trim, an armrest, a center console, a dashboard, a glove box, a seat, and / or a molding and a sliding member. (14) (B) (B1) one or more thermoplastic organic materials; (B2) silicone elastomer, and / or (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier containing (i) blending the uncured organopolysiloxane polymer (B3) and / or silicone elastomer (B2) components used to prepare the silicone composition with one or more thermoplastic organic materials (B1); (ii) dynamically vulcanizing the silicone composition to form a silicone elastomer (B2) during the preparation of the silicone elastomer (B2); and / or (iii) introducing (B3) during step (ii) or after step (iii) when preparing the silicone elastomer (B2); The method comprises the steps of: the masterbatch (B) comprises a total of 20 to 60 weight percent of components (B2)+(B3), based on the weight of (B1)+(B2)+(B3), and a total of 0.2 to 25 weight percent of crosslinked silicone elastomer is present in the thermoplastic elastomer composition, based on the weight of (A)+(B); and molding the thermoplastic material to form a molded article; A method for producing the molded article according to any one of (1) to (9) above, comprising: (15) The method according to (14) above, wherein the molded article is molded by extrusion molding, vacuum forming, injection molding, blow molding, 3D printing, or compression molding to produce a plastic part. (16) A method for manufacturing an assembly, comprising manufacturing a molded article according to (14) or (15) above, and fixing or positioning the molded article in frictional contact with a sliding member, wherein the molded article and the sliding member are configured to move relative to each other while remaining in frictional contact. (17) The use of thermoplastic silicone vulcanizates in masterbatches to reduce the occurrence of stick-slip interactions with thermoplastic materials. (18) The molded article of a thermoplastic material according to any one of (1) to (9) above, wherein the thermoplastic material is a thermoplastic elastomer material.

Claims

1. (A) one or more thermoplastic organic materials; (B)(B1) one or more thermoplastic organic materials; (B2) a crosslinked silicone elastomer, and, optionally (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier comprising A molded article of a thermoplastic material comprising a blend of Masterbatch (B) comprises 20 to 60 weight percent combined of components (B2)+(B3), based on the weight of (B1)+(B2)+(B3), and said thermoplastic material comprises 0.2 to 25 weight percent combined of crosslinked silicone elastomer, based on the weight of (A)+(B), said crosslinked silicone elastomer (B2) comprising: (B2a1) a diorganopolysiloxane having an average of at least two alkenyl groups per molecule; (B2a2) an organopolysiloxane having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule; (B2a3) a hydrosilylation catalyst; and (B2a5) an optional catalyst inhibitor; or A radical initiator (B2a4); or Silanol-terminated diorganopolysiloxane (B2b1), an organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, and Condensation catalyst (B2b3); and prepared by dynamic vulcanization of the diorganopolysiloxane (B2a1) or the diorganopolysiloxane (B2b1) is a gum having a Williams plasticity value of at least 100 mm / 100 as measured by ASTM D-926-08, The one or more thermoplastic organic materials (A) and (B1) are selected from polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate, ABS (acrylonitrile-butadiene-styrene), polystyrene (PS), and high impact polystyrene (HIPS), polyacrylate, styrene-acrylonitrile resin (SAN), and any blends thereof.

2. 2. The molded article of claim 1, wherein the uncured organopolysiloxane (B3) is present in an amount of 0.1 to 25% by weight of the masterbatch (B).

3. 3. The molded article of claim 2, wherein the one or more thermoplastic organic materials (A) and (B1) are selected from polycarbonate, ABS (acrylonitrile-butadiene-styrene), and any blends thereof.

4. 2. The molded article according to claim 1, wherein the molded article is an automobile part, a housing, a latch, a window opening mechanism, a wiper part, a sunroof part, a lever, a bush, a gear, a gearbox part, a pivot housing, a bracket, a zipper, a switch, a cam, a sliding element or plate, and a part of a door panel decorative trim, an armrest, a center console, a dashboard, a glove box, a seat; and / or a combination of parts that are in frictional contact with a sliding member.

5. 10. An assembly comprising the molded article of claim 1 in frictional contact with a sliding member, said molded article and said sliding member being configured to move relative to one another while remaining in frictional contact.

6. An assembly including a sliding member made of the molded product described in claim 1.

7. The assembly of claim 6 , wherein said sliding member is a non-plastic material.

8. 6. The assembly of claim 5, wherein the assembly is a combination of parts in frictional contact including door panel decorative trim, arm rest, center console, dashboard, glove box, seat or molding and sliding members.

9. (B)(B1) one or more thermoplastic organic materials; (B2) a crosslinked silicone elastomer, and optionally (B3) an uncured organopolysiloxane polymer; A masterbatch of a stick-slip modifier containing (i) blending the uncured organopolysiloxane polymer (B3) and the crosslinked silicone elastomer (B2) components used to prepare the silicone composition with one or more thermoplastic organic materials (B1); (ii) dynamically vulcanizing the silicone composition to form a crosslinked silicone elastomer (B2) in producing the crosslinked silicone elastomer (B2); and / or (iii) introducing (B3) during step (ii) or after step (iii) in producing said crosslinked silicone elastomer (B2), wherein masterbatch (B) comprises 20-60 wt. % combined components (B2)+(B3), based on the weight of (B1)+(B2)+(B3), and wherein there is present in the thermoplastic material a combined crosslinked silicone elastomer of 0.2-25 wt. %, based on the weight of (A)+(B); and molding said thermoplastic material to form a molded article; Including, The crosslinked silicone elastomer (B2) (i) a diorganopolysiloxane (B2a1) having an average of at least two alkenyl groups per molecule, (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, a hydrosilylation catalyst (B2a3), and an optional catalyst inhibitor (B2a5); or A radical initiator (B2a4); or Silanol-terminated diorganopolysiloxane (B2b1), an organopolysiloxane (B2a2) having at least two Si-bonded hydrogen atoms or at least three Si-bonded hydrogen atoms per molecule, and a condensation catalyst (B2b3); and prepared by dynamic vulcanization of The diorganopolysiloxane (B2a1) or the diorganopolysiloxane (B2b1) is a gum having a Williams plasticity value of at least 100 mm / 100 as measured by ASTM D-926-08. A method for producing the molded article according to claim 1.

10. 10. The method of claim 9, wherein the molded article is molded by extrusion, vacuum forming, injection molding, blow molding, 3D printing, or compression molding to produce a plastic part.

11. 10. A method of manufacturing an assembly comprising manufacturing a molded article according to claim 9 and fixing or placing the molded article in frictional contact with a sliding member, wherein the molded article and the sliding member are configured to move relative to each other while remaining in frictional contact.

12. 2. The molded thermoplastic article of claim 1, wherein the thermoplastic material is a thermoplastic elastomer material.

Citation Information

Patent Citations

  • Siloxane-modified thermoplastic material and preparation method thereof

    CN102924793A

  • Hardenable silicone-containing composition

    JP1983189257A

  • Production of thermoplastic elastomer

    JP2000109696A

  • Master batch comprising thermoplastic organic resin and silicone powder

    JP2000239398A

  • thermoplastic silicone elastomer

    JP2002505366A